Souping-Up Aharonov's Quantum Measurement Engine with a Plaga/Everett Apparatus (Global Journal of Science Frontier Research, 2021)
In this paper, two radical ideas from 30 years ago, via laser based, quantum measurement devices, will be revisited for the potential that they provide for exploration of the marriage of the themes of time travel and parallel universes, via their actual construction, as predicted